SPOP and CUL3 Modulate the Sonic Hedgehog Signal Response Through Controlled Degradation of GLI Family Transcription Factors - Umberger, Patricia A.; Ogden, Stacey K. (Frontiers in Cell and Developmental Biology, 2021)
The speckle-type POZ protein (SPOP) functions as a guardian of genome integrity and controls transcriptional regulation by functioning as a substrate adaptor for CUL3/RING-type E3 ubiquitin ligase complexes. SPOP-containing CUL3 complexes target a myriad of DNA-binding proteins involved in DNA repair and gene expression, and as such, are essential modulators of cellular homeostasis. GLI transcription factors are effectors of the Hedgehog (HH) pathway, a key driver of tissue morphogenesis and post-developmental homeostasis that is commonly corrupted in cancer. CUL3-SPOP activity regulates amplitude and duration of HH transcriptional responses by controlling stability of GLI family members. SPOP and GLI co-enrich in phase separated nuclear droplets that are thought to serve as hot spots for CUL3-mediated GLI ubiquitination and degradation. A similar framework exists in Drosophila, in which the Hedgehog-induced MATH (meprin and traf homology) and BTB (bric à brac, tramtrack, broad complex) domain containing protein (HIB) targets the GLI ortholog Cubitus interruptus (Ci) for Cul3-directed proteolysis. Despite this functional conservation, the molecular mechanisms by which HIB and SPOP contribute to Drosophila and vertebrate HH signaling differ. In this mini-review we highlight similarities between the two systems and discuss evolutionary divergence in GLI/Ci targeting that informs our understanding of how the GLI transcriptional code is controlled by SPOP and CUL3 in health and disease.